Research on mathematical abstraction literacy in China - Tang, Shiewei; Pereira, Jerito (CV. Pustaka Literasi Ilmiah, 2025)
Mathematical abstraction is the basic idea of mathematics, which is an important foundation for the formation of rational thinking, reflects the essential characteristics of mathematics, and permeates its generation, development, and application. The latest version of the general high school mathematics curriculum standard lists mathematical abstraction as the primary core literacy of the discipline, and mathematical abstraction literacy has become the focus of educational research. A number of scholars have researched mathematical abstraction literacy in senior high schools in China in recent years, but there is no literature that summarizes and compiles this aspect. This paper employs the literature analysis method to review and sort out the relevant literature on mathematical abstraction literacy and draws the following conclusions: (1) Previous research on mathematical abstraction literacy mainly contains five aspects, which are the connotation of mathematical abstraction, the current status quo of the level, the evaluation method, the influencing factors, and the strategies for the cultivation. (2) There are generally more studies on the connotation of mathematical abstraction, the current status of the level, and the cultivation strategy. However, in terms of influencing factors, the views in the existing literature are scattered, and no major influencing factors have been found. (3) The research methods are relatively single, with literature analysis or discursive methods predominating, especially the analysis of the influencing factors is not systematic and objective enough, lacks quantitative research for empirical evidence, and lacks targeted and practical cultivation strategies